2018
DOI: 10.1111/chd.12715
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for patent ductus arteriosus closure

Abstract: Even though up to 60% of premature infants less than 28 weeks gestation develop persistent patent ductus arteriosus (PDA), there remains controversy regarding if, when, and how to close the PDA. Failure to close the PDA has been associated with significant morbidity but no cause‐and‐effect has been proven for short‐term or long‐term outcomes in modern times. Surgical closure has the advantage of eliminating the PDA, but short‐term complications and long‐term adverse outcomes are worrisome. Intravenous indometh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 38 publications
(60 reference statements)
0
15
0
5
Order By: Relevance
“…Next to the ongoing discussion on the type of drug being either ibuprofen, indomethacin, or acetaminophen (117)(118)(119)(120)(121)(122)(123)(124), the timing of treatment initiation varies widely between studies, and might explain reported differences in efficacy. As spontaneous ductus closure increases with PNA, part of ductus closure reported in prophylactic and early treatment studies may be due to spontaneous closure rather than drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Next to the ongoing discussion on the type of drug being either ibuprofen, indomethacin, or acetaminophen (117)(118)(119)(120)(121)(122)(123)(124), the timing of treatment initiation varies widely between studies, and might explain reported differences in efficacy. As spontaneous ductus closure increases with PNA, part of ductus closure reported in prophylactic and early treatment studies may be due to spontaneous closure rather than drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sallmon H [33] observed that the complete closure rate following paracetamol administration is only 21.1% (4/19) in VLBW infants, in line with the closure rate of 27.5% (24/87) observed after paracetamol treatment in this study. Further, 3 other trials revealed that paracetamol was not as effective as ibuprofen, [34,35] and in a fourth trial PDA closure was only 18% with high-dose intravenous paracetamol in VLBW infants. [36]…”
Section: Discussionmentioning
confidence: 99%
“…As no other treatment option was available for PDA in Japan before 2018, intravenous IND administration remains the only conventional pharmacologic treatment to promote PDA closure in premature infants. However, concern remains regarding its safety, including its effects on renal, gastrointestinal, and cerebral perfusion, which may lead to complications such as transient or permanent renal dysfunction, NEC, gastrointestinal hemorrhage / perforation, and reduced cerebral intracellular oxygenation . In addition, hyperbilirubinemia, hypoglycemia, and thrombocytopenia are also the most common clinically encountered side effects of IND, especially in premature infants.…”
mentioning
confidence: 99%